Host the Holy Ghost - Savchuk, Vladimir (Vladimir Savchuk Ministries, 2023)
All believers in Christ have a relationship with the Holy Spirit, but not all believers have intimacy with Him. Holy Spirit was sent to lead you deeper in the knowledge of truth and give you the strength to overcome trials and the power to reach this world. In this book, Pastor Vladimir Savchuk takes you on a journey through discovering the communion with the Holy Spirit which belongs to everyone, not just the spiritually elite.